2022
DOI: 10.1021/acs.joc.1c03131
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Etherification of Less-Strained Cycloketoxime Esters Enabled by C–C Bond Cleavage

Abstract: We report a general, scalable, and convenient photochemical process for diversities of distal oxygenated nitriles from corresponding less-strained ketoxime esters allowing one-step introductions of ether and cyano groups, which avoids the utilization of toxic cyanide reagents. A wide range of ketoxime esters involving five-membered to eight-membered cycloketoxime esters and linear ketoxime esters participate smoothly under operately simple and mild conditions, affording structurally variable ring-opening produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Recently, Zhao reported the photoinduced etherification of cycloketoxime esters. 376 It was proposed that the photoexcited Ir( iii ) photocatalyst was quenched via SET by the cycloketoxime substrate to give an imine radical, which subsequently rearranged via C–C bond cleavage to give a distal radical (Scheme 100). This radical could be further oxidised by the photocatalyst to give the corresponding cation, which was intercepted by an alcohol to yield the ether product.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Recently, Zhao reported the photoinduced etherification of cycloketoxime esters. 376 It was proposed that the photoexcited Ir( iii ) photocatalyst was quenched via SET by the cycloketoxime substrate to give an imine radical, which subsequently rearranged via C–C bond cleavage to give a distal radical (Scheme 100). This radical could be further oxidised by the photocatalyst to give the corresponding cation, which was intercepted by an alcohol to yield the ether product.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Prompted by the results described above, we next evaluated other types of nucleophiles available in this photoinduced remote functionalization. , As shown in Scheme , it is worth mentioning that the γ-position of the alkene moiety upon visible-light irradiation could be functionalized with alcohol nucleophiles. It was found that methanol and ethanol were capable of serving as suitable nucleophiles, giving rise to products 5a and 5b , respectively, in moderate yields with >20/1 stereoselectivity.…”
mentioning
confidence: 99%